2016
DOI: 10.35872/jurkeb.v8i01.203
|View full text |Cite
|
Sign up to set email alerts
|

FAKTOR-FAKTOR YANG MEMPENGARUHI PERSALINAN PRETERM DI RSUD Prof. Dr. MARGONO SOEKARJO PURWOKERTO

Abstract: Tri Anasari1, Ika Pantiawati21) 2) Akademi Kebidanan YLPP PurwokertoE-mail: sariayu_nemen@yahoo.co.id, icha.pewe@yahoo.comABSTRAKPendahuluan: Persalinan preterm merupakan persalinan belum cukup umur di bawah usia kehamilan 37 minggu dan berat bayi kurang dari 2500 gr. Dampak yang dapat ditimbulkan dari kejadian persalinan preterm antara lain hipotermi, asfiksia, ikterik, infeksi dan pertumbuhan retardasi janin. Dampak tersebut merupakan penyebab utama kematian pada bayi. Persalinan preterm di RSUD Margono Soek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
0
9
2
8
Order By: Relevance
“…A retrospective study showed that women aged 21-35 years more often suffered from mastitis than women on other age groups; below 21 years or over 35 years. 5 However, our results showed there is no association between age and the incidence of mastitis. Hence this variable is not necessarily a protective factor for the condition.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…A retrospective study showed that women aged 21-35 years more often suffered from mastitis than women on other age groups; below 21 years or over 35 years. 5 However, our results showed there is no association between age and the incidence of mastitis. Hence this variable is not necessarily a protective factor for the condition.…”
Section: Discussioncontrasting
confidence: 65%
“…However, mastitis can also happen at any time during breastfeeding, and around 3% of women with untreated mastitis may develop a complication such a breast abscess. 5 The failure to provide exclusive breastfeeding is often caused by the specificmedical condition, such as the blockade of mammary gland under the nipple. This can cause a decrease in milk ejection.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found a p-value of 0.003, which means that there is a relationship between nutritional status and preterm labor. If the mother at the time before and during pregnancy lacks nutritional intake and weight gain is less at risk of causing preterm labor [28].…”
Section: K Weight Gain During Pregnancymentioning
confidence: 99%
“…Ibu hamil usia reproduktif merupakan usia aman untuk kehamilan dan persalinan adalah usia 20-35 tahun (Depkes, 2009). Akan tetapi, berdasarkan beberapa penelitian mengungkapkan bahwa usia reproduktif (20-35 tahun) lebih banyak mengalami kejadian persalinan prematur daripada usia berisiko (<20 dan >35 tahun) (Anasari & Pantiawati, 2016;Ningrum et al, 2017).…”
Section: Pendahuluanunclassified